If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(2k+2)=7(-3k)
We move all terms to the left:
7(2k+2)-(7(-3k))=0
We multiply parentheses
14k-(7(-3k))+14=0
We calculate terms in parentheses: -(7(-3k)), so:We get rid of parentheses
7(-3k)
We multiply parentheses
-21k
Back to the equation:
-(-21k)
14k+21k+14=0
We add all the numbers together, and all the variables
35k+14=0
We move all terms containing k to the left, all other terms to the right
35k=-14
k=-14/35
k=-2/5
| 7n-27=61 | | 8x/9=x-3 | | x-30=52 | | 10-g/5=13 | | 7^2x=-49 | | -5=x-7-9 | | 4z/z+4=5 | | 40+0.22×m=89 | | h=3=8 | | 3-h=8 | | n/7+10=14 | | 3=n/4-5 | | m4=m5 | | 3(v+1)=-6v-33 | | 13y+28=17y | | 6x+12=10x-44 | | 9j+16=34 | | t+68=14t-10 | | 8-4.2=v | | 10x×5(2x-2)×4(x1)=1 | | mA=10 | | 4z-20=z+40 | | 4z-60=z | | 2w=7w-60 | | 9(p−87)=45 | | 9(j−87)=45 | | 0.25m=8 | | 6x-20=3x+45} | | 5^2x^-4-1=0 | | 4y-4y=-6 | | -10k+6k=-40 | | 4(w)=168 |